Evaluation of the reference value for the Montenegro skin test - Cissiara Manetti Skraba; Tatiane França Perles de Mello; Raíssa Bocchi Pedroso; Érika Cristina Ferreira; Izabel Galhardo Demarchi; Sandra Mara Alessi Aristides; Maria Valdrinez Campana Lonardoni; Thaís Gomes Verzignassi Silveira (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
Abstract:INTRODUCTION:The Montenegro skin test (MST) has good clinical applicability and low cost for the diagnosis of American tegumentary leishmaniasis (ATL). However, no studies have validated the reference value (5mm) typically used to discriminate positive and negative results. We investigated MST results and evaluated its performance using different cut-off points.METHODS:The results of laboratory tests for 4,256 patients with suspected ATL were analyzed, and 1,182 individuals were found to fulfill the established criteria. Two groups were formed. The positive cutaneous leishmaniasis (PCL) group included patients with skin lesions and positive direct search for parasites (DS) results. The negative cutaneous leishmaniasis (NCL) group included patients with skin lesions with evolution up to 2 months, negative DS results, and negative indirect immunofluorescence assay results who were residents of urban areas that were reported to be probable sites of infection at domiciles and peridomiciles.RESULTS:The PCL and NCL groups included 769 and 413 individuals, respectively. The mean ± standard deviation MST in the PCL group was 12.62 ± 5.91mm [95% confidence interval (CI): 12.20-13.04], and that in the NCL group was 1.43 ± 2.17mm (95% CI: 1.23-1.63). Receiver-operating characteristic curve analysis indicated 97.4% sensitivity and 93.9% specificity for a cut-off of 5mm and 95.8% sensitivity and 97.1% specificity for a cut-off of 6mm.CONCLUSIONS:Either 5mm or 6mm could be used as the cut-off value for diagnosing ATL, as both values had high sensitivity and specificity.